2011
DOI: 10.2174/138161211797416093
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Tauopathy by the Drug Candidates NAP (Davunetide) and D-SAL: Biochemical, Cellular and Behavioral Aspects

Abstract: Activity-dependent neuroprotective protein (ADNP) is essential for brain formation and partial deficiency in ADNP results in cognitive deficits coupled with tauopathy and neuronal cell death. Our previous results indicated that a peptide snippet from ADNP, NAPVSIPQ (NAP, generic name, davunetide) can restore in part ADNP deficiencies. NAP interacts with tubulin and this interaction is displaced by the NAP related peptide that is derived from activity-dependent neurotrophic factor (ADNF), SALLRSIPA (SAL) and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 86 publications
1
27
0
Order By: Relevance
“…These peptides do not exhibit stereo-selectivity59. The more stable, all D-amino acid SAL (D-SAL) showed efficacy in-vivo and in-vitro models of disease3031. In a model of fetal alcohol syndrome (FAS), administration of both D-NAP and D-SAL reduced fetal demise, however, no significant differences between combination and individual drug treatments were seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These peptides do not exhibit stereo-selectivity59. The more stable, all D-amino acid SAL (D-SAL) showed efficacy in-vivo and in-vitro models of disease3031. In a model of fetal alcohol syndrome (FAS), administration of both D-NAP and D-SAL reduced fetal demise, however, no significant differences between combination and individual drug treatments were seen.…”
Section: Discussionmentioning
confidence: 99%
“…SAL is derived from the glial precursor protein, activity dependent neurotrophic factor (ADNF). It exhibits similar neuroprotective capabilities to NAP in numerous animal and cell models of injury and disease2728293031.…”
mentioning
confidence: 97%
“…Capitulating on the NAP target, we have designed SKIP (Ser-Lys-Ile-Pro) and shown that it mimics NAP protection, as well as protects ADNP-deficient impairment in axonal transport (Amram et al 2016). Together with new diagnostic tools, such as changes in blood ADNP in parallel to brain cognitive decline , this and other pipeline products (Shiryaev et al 2011;Gozes et al 2014a, b) are ready for future development, at the basic mechanistic understanding and at the clinical frontiers. …”
Section: Mechanism and Future Horizonsmentioning
confidence: 99%
“…Other possible mechanisms of neuroprotection include the Bcl2 mitochondrial intrinsic signaling pathway, which regulates cell survival and apoptosis [70] and the extrinsic JNK signaling pathway [71]. The all D-amino acid analogue of ADNF-9 was found to protect against Aβ tau hyperphosphorylation, in early events, in vitro and in vivo, with regards to neuroprotection and maintenance of neuronal organization [72]. ADNF-9 was tested in in vitro and in vivo ALS models [58].…”
Section: Adnf-9 Peptide Derived From Activitydependent Neurotrophic Fmentioning
confidence: 99%